134 Does a Purely Occipital Lobe Stroke Lead to Significant Long Term Disability and Handicap?. (16th September 2019) - Davey, Naomi; McNally, Sarah; Donnelly, Kerri; Kate Meagher, Mary; Noone, Imelda; Cassidy, Tim
Abstract: Background: Occipital lobe strokes are characterised by a visual field deficit (VFD) and the absence of a motor deficit. A persistent VFD may have significant long-term implications for a patient and their lifestyle. Our aim was to assess the overall impact of these events particularly patients' ability to return to driving. Methods: All patients admitted with an acute occipital lobe stroke to a Dublin teaching hospital in 2017 were identified. Case notes were retrospectively reviewed to identify patients' pre-stroke function, stroke pathology, neurological losses and further vascular events. A follow up phone call was made 18 months after the event to assess if previous drivers had returned to driving and required the installation of formalised home supports after discharge. Results: In 2017, 37 of 311 stroke patients admitted had a confirmed occipital lobe stroke. 33 of these patients (89.1%) had ischemic events. The median age was 76 (50-93) years old. Twenty-nine patients were able to undergo formal cognitive testing; the median Montreal Cognitive Assessment (MOCA) was 18 (2-29). 15 patients (40.5%) had underlying Atrial Fibrillation with one (6.7%) of this cohort being identified post discharge; 14 (85.7%) of those patients with ischemic strokes were anticoagulated for atrial fibrillation. The median length of stay was 33.9 days, with a range of 2-391 days. Further vascular events occurred in 2 (5.8%) of the patients. A follow up phone call was made to the 15 patients who drove prior to their event. 12 patients (80%) could not resume driving due to persistent VFD. One (7%) of the previous drivers had a home care package installed since discharge. Conclusion: A persistent VFD results in long term problems including an increased risk of further vascular events, a reduction in overall independence and quality of life following an occipital lobe stroke. This study has led to a business plan for a dedicated hemianopia clinic.